Intermittent Fasting as New Approaches as Anti Aging for Preventing Age-associated Diseases - Yesi Rosalia; I Wayan Juli Sumadi (Postgraduate, University of Mataram, 2023)
The aging process is inherently linked to an increased susceptibility to various chronic conditions, such as cardiovascular diseases, diabetes, and neurodegenerative disorders. The aim of this research is to delves into the current body of knowledge surrounding intermittent fasting and its potential implications in preventing age-related diseases. The methodological approach used in this research is systematic review. Research search using PRISMA strategy by searching journal articles from various databases including Scopus, Proquest, Science Direct, CINAHL, and Google Scholar in the last five years from 2019 to 2023. The results of PRISMA found 333 articles identified through the five databases contained in research methods and screened through titles. Result this research is the promising role of intermittent fasting in promoting anti-aging effects and preventing age-associated diseases through its multifaceted influence on cellular and molecular mechanisms. As an innovative avenue, intermittent fasting holds the potential to revolutionize strategies aimed at enhancing healthy aging and longevity. intermittent fasting as new approachesÂ as anti aging for preventing age-associated diseases Â